Phenological Changes in Alpine Grasslands and Their Influencing Factors in Seasonally Frozen Ground Regions Across the Three Parallel Rivers Region, Qinghai-Tibet Plateau - Wang, Chun-Ya; Wang, Jin-Niu; Wang, Xu-Feng; Luo, Dong-Liang; Wei, Yan-Qiang; Cui, Xia; Wu, Ning; Bagaria, Priyamvada (Frontiers in Earth Science, 2022)
The vulnerability of alpine ecosystems makes their phenology sensitive and responsive to climate change. In this study, Moderate Resolution Imaging Spectroradiometer (MODIS) Normalized Difference Vegetation Index (NDVI) data (2000-2019) across the Three Parallel Rivers region (TPRR) in the southeast of the Qinghai-Tibet Plateau (QTP), were used to extract information on three key phenological parameters of alpine grasslands about their spatio-temporal heterogeneity in seasonally frozen ground and their response to climate change, using a dynamic threshold method from the TIMESAT 3.2 (i.e., start of growth season (SOS), end of growth season (EOS), and length of growing season (LOS)). The results revealed that under increasingly warming and drying climate, SOS was advanced by 0.16 d yr-l while EOS was delayed by 0.08 d yr-l, which led to the extension of LOS (slope=0.07d yr-l). The spatial distribution of the parameters was significantly different between the northern and southern regions. Moreover, with increasing elevation from southeast to the northwest, the multi-year mean SOS gradually delayed from 100 to 160 d. However, EOS advanced as a whole (from 320d to 280d), and LOS gradually extended (from 130 to 210 d). In addition, SOS had a significant negative correlation with the annual mean temperature (AMT) and a positive correlation with the annual precipitation amount (ATP). LOS had a significant positive correlation with AMT but a negative correlation with ATP, given that, EOS had no significant correlation with climatic factors. Both freezing and thawing indexes were significantly affected by elevation, and the air/ground surface freezing index showed a downward trend from north to south, while the air/ground surface thawing index showed an upward trend over the past 20 years. There was a strong correlation between the freezing/thawing index and vegetation phenology. SOS was negatively correlated with both air/ground surface freezing and thawing index, and EOS and LOS were negatively correlated with air/ground surface freezing index while positively correlated with thawing index.